Differences Levels of Sodium, Potassium, Calcium, and Magnesium Before and After Cisplatin Administration in Child with Osteosarcoma - Wardhana, Hendra; Riza, Muhammad; Umma, Husnia Auliyatul (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Cisplatin is one of the most commonly used cytostatic chemotherapy agents, especially in patients with solid tumors such as osteosarcoma. The exact mechanism of whether and how cisplatin causes electrolyte disturbances is still unclear. This study aims to determine the differences in levels of sodium, potassium, calcium, and magnesium with the administration of cisplatin in children with osteosarcoma.Subjects and Method: This was an analytical retrospective study using secondary data in the form of medical records. The sample size in this study was calculated by the single proportion for